Intrapreneurship and Business Performance among Micro, Small and Medium Enterprises in the Philippines - Denuevo, Althea; Libo-on, Rowena (Indonesian Association for Public Administration, 2025)
This study aimed to evaluate the intrapreneurship and business performance of micro, small, and medium enterprises in Iloilo City, Philippines. Intrapreneurship includes new business ventures, innovation, self-renewal, and proactiveness. Business performance includesfinancial and market performance . Survey data we re collected from 162 enterprise owners or managers from industries such as manufacturing, wholesale, retail trade and repair services, accommodation/food services, financial and insurance services, and others. The results confirm a positive correlation between intrapreneurship and business performance. A significant difference was detected in the level of innovativeness when enterprises were grouped according to their business type. The majority of the enterprises were operating for between 5 and 14 years, mostly micro enterprises and sole proprietorships. Marketing and operations activities were highly practiced by the enterprises. Support from other entities was rated the highest in comparison with partnerships with academe and government support. The highest mean score for proactiveness indicates a high level of intrapreneurship. Medium enterprises and those operating for 45 or more years have very high market performance. To encourage an intrapreneurship culture within the organization, where creativity and innovation can be fostered to enhance business performance, an efficient and effective intrapreneurship program is recommended.